# algebra

posted by .

1) 27x^3+8

2) 3x^2-x-4

• algebra -

The first is the sum of two cubes, you have a formula for that.
The second:

(3x -4)(x +1)

• algebra -

a^3 + b^3 = (a+b)(a^2-ab+b^2)
here
a = 3x
b = 2
You take it from there

(3x-4)(x+1)

## Similar Questions

1. ### Math - Logarithmic

Solve: 2log_3(x) - log_3(x-2) = 2 My Work: log_3(x^2) - log_3(x-2) = log_3(3^2) log_3 [(x^2) / (x-2)] = log_3(27) (x^2) / (x-2) = 27 x^2 = (x-2)(27) x^2 = 27x - 54 x^2 - 27x = -54 27x = -54 x = -2 Textbook Answer: 3 or 6 Where did …
2. ### rational exponents

Express cube root 27x^4y^6 using rational exponents (27x^4y^6)1/3 (27^1/3)(x^4/3)(y^6/3) stuck. I think the final answer is 9x^3/4(y^2) I don't know where to put the parentheses to break it up so I hope yall understand what it's suppose …
3. ### Math

[(6x+1)^3][(27x^2+2)-(9x^3+2x)](3)[(6x+1)^2](6) over [(6x+1)^3]^2 Help me simplify please?

27x^2-1/3y^2
5. ### Algebra (Intermediate)

5. Solve using the elimination method. Show your work. If the system has no solution or an infinite number of solutions, state this. 9x + 6y = 60 -27x Ð 18y = -180 Here's where I am at now: 9x(3) + 6y(3) = 60 27x +18y + 60 27 x + …
6. ### algebra 2

Factor: 27X^2-90X+27
7. ### Algebra

(8x^3 - 14x^2 - 27x - 9) / (4x + 3)
8. ### algebra

solve for "x" in the following equation: 27x-3(x-6)= 6 F: -2 G: -1/2 H: 1/2 J: 2
9. ### algebra equations

1) 3x(4x-9)= 12x^2-27x 2) 4x^2(x+6)= 3) 2x^2(15x^3-10)